2021
DOI: 10.1021/acs.macromol.1c01959
|View full text |Cite
|
Sign up to set email alerts
|

Highly Refractive Polyimides Derived from Efficient Catalyst-Free Thiol–Yne Click Polymerization

Abstract: Polyimides (PIs), owing to their inherent high refractive index and excellent physical properties, are required in advanced optical applications. They are traditionally synthesized through conventional two-step polycondensation, followed by hightemperature or chemical imidization, inevitably increasing energy consumption, environmental pollution, and production duration. Herein, for the first time, we synthesized PIs consisting of vinylene sulfide linkages via an efficient catalyst-free thiol−yne click polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Thiolactone is a five-membered cyclic sulfur compound, which can be opened by a primary amine in the absence of catalysts and simultaneously release a thiol in situ . The exposed thiols are subsequently captured through thiol-ene/yne, thiol-acrylate, thiol-epoxy, and thiol-isocyanate reactions to achieve a one-pot two-step double functionalization. Given the advantages of simplicity, high efficiency, and no byproducts of this strategy, thiolactone chemistry provides an effective platform for side-chain modification of the polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Thiolactone is a five-membered cyclic sulfur compound, which can be opened by a primary amine in the absence of catalysts and simultaneously release a thiol in situ . The exposed thiols are subsequently captured through thiol-ene/yne, thiol-acrylate, thiol-epoxy, and thiol-isocyanate reactions to achieve a one-pot two-step double functionalization. Given the advantages of simplicity, high efficiency, and no byproducts of this strategy, thiolactone chemistry provides an effective platform for side-chain modification of the polymers.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, unlike conventional two-step polycondensation, Zhang et al creatively synthesized the functional polyimides (PIs) with good optical properties and robust mechanical properties by spontaneous thiol-yne click polymerization (Figure 1C). 29 The resultant PIs showed good tensile strengths as high as 114.9 MPa, high glass transition temperatures and thermal decomposition temperatures (up to 238 o C and 381 o C, respectively). Notably, one of the prepared polymer films, PI BPADA-TBT, demonstrated a comparable or even preferable refractive index and much lower birefringence than most of the previously reported PIs.…”
Section: Scheme 1 Four Categories Of Thiol-yne Click Polymerization B...mentioning
confidence: 94%
“…The introduction of sulfur atoms effectively raised the refractive index of polymers, making thiol-yne click polymerization promising for optical applications. 29 It's found that both vinyl ether bond and enamine bond are labile under weak acidic conditions, 44,59 and in addition, the enamine bond has an exceptional 1 O2responsiveness. 61 These unique characteristics make the corresponding polymers inherently degradable in the presence of weak acid or 1 O2 and has led to the widespread applications of hydroxyl/amino-yne click polymerizations in the construction of controlled release drug carriers.…”
Section: Functionality Explorationmentioning
confidence: 99%
“…Selecting a functional polymer as the polymer phase, such as a polyimide with excellent thermal and chemical resistance, , can introduce new functionalities to the hybrid nanocomposite. Previously, we fabricated polyimide nanocomposites exhibiting a combination of low-density as well as heat and fracture resistance that was useful for lightweight and high-temperature applications .…”
Section: Introductionmentioning
confidence: 99%